IN VITRO ANTIBACTERIAL ACTIVITY OF BIOSYNTHESIZED SILVER NANOPARTICLES FROM ETHYL ACETATE EXTRACT OF HYDROCOTYLE SIBTHORPIODES AGAINST MULTI DRUG RESISTANT MICROBES. - Garg, Manashi; Devi, Banasmita; Devi, Rashna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Hydrocotyle sibthorpiodes is known to contain several phytoconstituents which are constantly involved in the formation of Silver nanoparticles that may affect several multi-drug resistant microbes. Therefore, the study was undertaken to evaluate the efficacy of different concentration of nano silver solution on three bacterial isolates. It was also aimed to qualitatively assess the different phytoconstituents responsible for the synthesis. Methods: Three bacterial isolates of Klebsiella pneumonia, Pseudomonas aeroginosa and Staphylococcus aureus were identified. Synthesis of AgNPs with different concentration (2/4/6/8/10μl/ml) was done and applied to the selected isolates. The phytochemical compounds of the ethyl acetate extract were assayed by several colored reactions qualitatively. Results: The size and stability biosynthesis of the metallic silver nanoparticles were confirmed by photophysical characterization as well as SEM (Scanning Electron Microscopy), XRD (XRay Diffraction), Zeta potential and DLS (Dynamic Light Scattering) with an average size of 13.37 ±10 nm. The increasing concentration of the particle solution showed significant inhibition zone for all the three isolates viz., Klebsiella pneumonia, Pseudomonas aeroginosa and Staphylococcus. aureus showing the value of 3.0±0.17, 2.7±0.32 and 3.6±0.57 respectively for 10 μl/ml concentration. Phytochemical screening of the whole plant extract also revealed an array of bioactive compounds which may have an effective role in the reduction process. Conclusion: The study demonstrated a simple, efficient and eco-friendly synthesis of stable silver nanoparticles from the ethyl acetate extract of Hydrocotyle sibthorpiodes having fairly superior antimicrobial activity against human pathogens.